Crop Rotation An Approach to Secure Future Food - Ouda, Samiha (Springer International Publishing, 2018)
This book tackles the issue of using crop rotation to increase food production and secure it for the growing population of the future. Crop rotation can be a solution of food gaps in the developing counties. Crop rotation plays an important role in attaining soil sustainability and in controlling pests and weeds. It can alleviate damage caused by climate change by reducing losses in productivity of the crops, minimizing soil fertility loss and increase irrigation water productivity. This book also includes the reviews of a large number of crop rotations that have been published internationally, and additionally, the crop rotations that have been implemented in Egypt have a unique characteristic to them and therefore, a large number of those reviews have also been included.